Analisis Peran Bantuan Dana Produktif Usaha Mikro (BPUM) terhadap Keberlangsungan UMKM Kecamatan Tungkal Ilir pada Tahun 2020 dan 2021 - Muhammad Doni; Sissah Sissah; Eri Nofriza (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
There are three issues studied in this thesis, namely: The role of Micro Business Productive Fund Assistance (BPUM) on the sustainability of MSMEs, procedures for distributing Micro Business Productive Fund Assistance (BPUM) to MSMEs, and maintaining business continuity during the Covid-19 pandemic. The aim of this research is to determine the role of Micro Business Productive Fund Assistance (BPUM) on the sustainability of MSMEs, to find out the procedures for distributing Micro Business Productive Fund Assistance (BPUM) on the sustainability of MSMEs and to find out how to maintain business continuity during the Covid-19 pandemic in the sub-district. Tungkal Ilir in 2020 and 2021. To reveal this problem in depth and comprehensively, researchers used a qualitative approach by collecting data using observation, interviews and documentation. The data analysis technique used is field analysis using the Miles and Huberman interactive model including data reduction, data display, data verification. From the research results, it can be concluded that the role and potential of BPUM are: The BPUM program will be a temporary buffer for micro businesses to reduce the negative impact of social restrictions/pandemic, encouragement to increase MSME data, accuracy of targeting of aid distribution and encouragement to BPUM beneficiaries related to licensing, certification and taxation systems. The procedures for distributing BPUM are listed in Chapter IV, Article 7 of the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 6 of 2020 concerning General Guidelines for National Support for Economic Recovery in the context of threats that endanger the nation's economy and saving the national economy during the COVID-19 virus. And there are three factors that play a role in maintaining business continuity during the COVID-19 pandemic, namely the ability to innovate, manage customers and return on investment.